Synthesis and applications of ruthenium(II)quaterpyridinium complexes and Poly-N-isopropylacrylamide/ acrylic acid copolymers - Siyambalagoda Gamage, Pubudu Hasanka (Kansas State University, 2010)
Tris-homoleptic ruthenium(II)-quaterpyridyl and quaterpyridinium complexes, with +8 and +14 charge were synthesized by utilizing high pressure reaction pathway. These complexes have diameters ranging from 1.82 to 4.55 nm according to the molecular modeling calculations. These ruthenium complexes are highly luminescent and contain long excited state life times. The novel ruthenium(II)-quaterpyridinium complexes exhibit superior reactivity as sensitizer-relay-assemblies (SRA‟s) in sacrificial systems for water and carbon dioxide reductions, while harvesting the ultraviolet- and most of the visible fraction of the incident solar spectrum. Ru(II)-quaterpyridinium complexes and Pd/TiO2 catalysts were successfully used as the catalytic system for the photo catalytic reduction of water and carbon dioxide to hydrogen and methane respectively. Phosphonate-tethered Ru(II)-quaterpyridinium complexes were synthesized from Ru(II)-tris-quaterpyridyl complexes. These complexes form stable adhesive layers on indium tin oxide (ITO) electrodes. A series of differential pulse voltammetry experiments were carried out to measure the ground state and excited state redox potentials of all the Ru(II)quaterpyridinium complexes. The reductive potentials obtained were compared with the reductive potentials of CO2 to CH4 and H2O to H2 reductions. The measurements obtained from the experiments confirmed that it is possible to thermodynamically oxidize water and reduce CO2 by using phosphonate-tethered Ru(II)-quaterpyridinium complexes. These complexes are successfully utilized as prototypes for mycobacterial channel blockers. The Ru(II) complexes show distinct changes in their luminescence spectra when bound to the porin MspA from M. smegmatis, which is a non-pathogenic relative of M. tuberculosis. By using HPLC, we have determined binding constants of the Ru(II)-complexes to MspA in phosphate buffer (0.05 M, pH = 6.8) ranging from 5.2 x 109 M-1 (Ru-C2) to 1.8 x 109 M-1 (Ru-C4). Our findings indicate that channel blocking is a promising treatment strategy for mycobacterial infections. Poly-N-isopropyl-acrylamide/acetic acid copolymers were synthesized and characterized by elemental analysis and gel permeation chromatography. The average composition of the copolymers determined from CHN analysis is in excellent correlation with the feed composition indicating that the radical polymerization process is indeed statistical. Crosslinking of individual polymer chains permitted the generation of ultraflat layers on Mica surfaces by a simple spin-casting procedure, which are able to host the mycobacterial channel protein MspA, while retaining its channel function.
Keywords: Artificial photosynthesis; MspA; Channel blockers; Solar hydrogen; Ruthenium-quaterpyridinium complexes; Poly-N-isopropyl-acrylamide; Chemistry, Organic (0490)